Pengaruh Pelatihan Kerja dan Penilaian Kinerja Terhadap Kinerja Karyawan Direktorat Umum dan SDM BPJS Ketenagakerjaan Pusat - Gita Maharani; Syarif Ali; Zackharia Rialmi (Universitas Islam Kadiri, 2021)
This research is a quantitative study that aims to determine and prove the effect of job training and performance appraisals on employee performance. The sample used in this study were all employees of the Direktorat Umum dan SDM BPJS Ketenagakerjaan Pusat amounting to 100 employees. Data collection by questionnaire via google form. The analysis technique used was inferential analysis and data processing was carried out through SPSS Statistics 23 with a significant level of 5% (0,05). The results of the test obtained (1) job training has an effect on employee performance, (2) performance appraisal has an effect on employee performance, (3) job training and performance appraisal simultaneously have an effect on employee performance. Keywords: job training, performance appraisal, and employee performance.